2013
DOI: 10.1007/s11060-013-1316-y
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of erlotinib in patients with relapsed gliobastoma multiforme who expressed EGFRVIII and PTEN determined by immunohistochemistry

Abstract: Epidermal growth factor receptor gene (EGFR) alteration is a common feature in most of glioblastoma multiforme (GBM). Robust response of anti-EGFR treatments has been mostly associated with the EGFR deletion mutant variant III (EGFRvIII) and expression of PTEN. We have performed a prospective trial in order to confirm the efficacy of erlotinib treatment in patients with relapsed GBM who expressed EGFRvIII and PTEN. All patients included in the trial were required to be PTEN (+++), EGFR (+++) and EGFRvIII (+++)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Our findings are consistent with those of other studies, indicating that GBM patients not selected for any biological characteristic show modest response to EGFR inhibitors . The association of EGFR amplification with GBM tumors led to early optimism that EGFR inhibition would be beneficial.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of other studies, indicating that GBM patients not selected for any biological characteristic show modest response to EGFR inhibitors . The association of EGFR amplification with GBM tumors led to early optimism that EGFR inhibition would be beneficial.…”
Section: Discussionsupporting
confidence: 92%
“…In a series of 41 patients, Haas-Kogan et al reported observing 8 responses in individuals who expressed high levels of egfr and low levels of Akt. A recent prospective study of erlotinib 55 did not reproduce the latter findings. Conducted in patients with recurrent gbm and with co-expression of egfrviii and pten determined by immunohistochemistry, that study reported an os of 7 months and a pfs of 3 months.…”
Section: Inhibitors Of Egfr: Monotherapy or Combination?mentioning
confidence: 85%
“…Studies reporting the prognostic or predictive value of EGFRvIII are listed in Table 1 [8,15,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]. We found 17 studies considering 1656 GBM patients overall.…”
Section: Epidermal Growth Factor Receptor Variant IIImentioning
confidence: 99%